Characterization of triple‐negative breast cancer preclinical models provides functional evidence of metastatic progression. Issue 8 (2nd April 2019) - Arroyo‐Crespo, Juan J.; Armiñán, Ana; Charbonnier, David; Deladriere, Coralie; Palomino‐Schätzlein, Martina; Lamas‐Domingo, Rubén; Forteza, Jerónimo; Pineda‐Lucena, Antonio; Vicent, María J.
Abstract : Triple‐negative breast cancer (TNBC), an aggressive, metastatic and recurrent breast cancer (BC) subtype, currently suffers from a lack of adequately described spontaneously metastatic preclinical models that faithfully reproduce the clinical scenario. We describe two preclinical spontaneously metastatic TNBC orthotopic murine models for the development of advanced therapeutics: an immunodeficient human MDA‐MB‐231‐Luc model and an immunocompetent mouse 4T1 model. Furthermore, we provide a broad range of multifactorial analysis for both models that could provide relevant information for the development of new therapies and diagnostic tools. Our comparisons uncovered differential growth rates, stromal arrangements and metabolic profiles in primary tumors, and the presence of cancer‐associated adipocyte infiltration in the MDA‐MB‐231‐Luc model. Histopathological studies highlighted the more rapid metastatic spread to the lungs in the 4T1 model following a lymphatic route, while we observed both homogeneous (MDA‐MB‐231‐Luc) and heterogeneous (4T1) metastatic spread to axillary lymph nodes. We encountered unique metabolomic signatures in each model, including crucial amino acids and cell membrane components. Hematological analysis demonstrated severe leukemoid and lymphoid reactions in the 4T1 model with the partial reestablishment of immune responses in the immunocompromised MDA‐MB‐231‐Luc model. Additionally, we discovered β‐immunoglobulinemia and increased basal levels of G‐CSF correlating with a metastatic switch, with G‐CSF also promoting extramedullary hematopoiesis (both models) and causing hepatosplenomegaly (4T1 model). Overall, we believe that the characterization of these preclinical models will foster the development of advanced therapeutic strategies for TNBC treatment, especially for the treatment of patients presenting both, primary tumors and metastatic spread. Abstract : What's new? Triple‐negative breast cancer (TNBC), an aggressive, metastatic, and recurrent breast cancer subtype, currently lacks adequately described spontaneously metastatic preclinical models that faithfully reproduce the clinical scenario. Here, the authors provide an in‐depth comparative analysis of two preclinical spontaneously metastatic TNBC orthotopic models, MDA‐MB‐231‐Luc and 4T1. The results reveal a metastatic switch in both models with immune system activation and serum‐protein profile reconfiguration, which may support resistance to treatment and recurrence in TNBC. The authors also identify critical functional biomarkers and metabolomic signatures for metastatic progression that may facilitate the development of anticancer therapeutics.